Between Worlds — Bolesław Leśmian’s Mirrors - Podwysocka-Modrzejewska, Jowita (Lustro, 2020)
The text concerns the various use of the mirror symbol and its function by Bolesław Leśmian in his works. A mirror in Leśmian’s poetry can be a gateway to another — magic world, thanks to which you can know the truth about the world and about yourself. It can also act as an apotropeion.The characteristics of the mirror used by the author of Łąki agree with those rooted in culture — folk beliefs, but also in fairy tales. Specific tales are indicated, but also other works in which a mirror appears.In his poetry, Lesmian uses many times more than one of the functions attributed to the mirror, which is an unusual subject. The poet usually bases his poems on the aforementioned uniqueness of the object, allowing the figures to be transferred to the other world by means of the mirror.